Training load, injury burden, and team success in professional rugby union: Risk versus reward - West, S. W.; Williams, S.; Kemp, S. P. T.; Eager, R.; Cross, M. J.; Stokes, K. A. (Journal of Athletic Training, 2020)
Context: Individual and team injury burden and performance are 2 key considerations facing practitioners in the daily prescription of an athlete's training load. Whereas a considerable number of researchers have examined univariate relationships between training load and performance, training load and injury, or injury and performance, few investigators have examined all 3 concurrently. Objective: To assess the association among training load, injury burden, and performance in professional rugby union. Design: Descriptive epidemiology study. Setting: The English Premiership competition. Patients or Other Participants: Individual injury and training load data, as well as team performance data, were captured during the 2015-2016 (n = 433 players) and 2016-2017 (n = 569 players) seasons. Main Outcome Measure(s): Data were aggregated into team average scores for each week, including weekly (acute) load, smoothed chronic load, changes in load, injury burden, and weekly performance. Linear mixed modelling techniques were used to assess the association among measures. Results: Injury burden was negatively associated with performance, with a high weekly burden associated with a likely harmful (P = .01) decrease in performance. Training load measures displayed only trivial associations with performance. Only the acute:chronic workload ratio measure was clearly associated with injury burden, with a possibly harmful effect (P = .02). Both squad size and player availability were associated with only trivial changes in performance. Conclusions: Whereas no association between average training load and performance existed, associations between training load and injury burden and between injury burden and performance were clear. Further investigation using more sensitive and individualized measures of load, performance, and injury may elicit a clearer relationship and should be considered for future work.